A Study on Bipolar Transurethral Resection of Prostate (TURP) versus Transurethral Resection and Electrovaporization (TURP-TUVP) Sandwich Procedure - Gain, Sandipan; Naser, Md Fazal; Hooda, Md Nurul (Bangladesh Journal of Urology, 2022)
Background: TURP is the gold standard for the endoscopic treatment of BPH. Nonetheless, it remains associated with significant morbidity, especially in terms of hemorrhage leading to possible blood transfusion and delayed hospital discharge. TUVP is associated with reported improvements in subjective and objective measures but a high rate of postoperative irritative symptoms and lack of tissue for histologic examination. The concept behind TURP and TUVP sandwich procedure is to overcome the drawbacks of the two procedures. Objective: To compare the outcome of bipolar transurethral resection of prostate (TURP) and bipolar transurethral resection and electrovaporization of prostate (TURP-TUVP) sandwich procedure in patient with benign prostatic hyperplasia. Methods: This quasi experimental study was conducted in the Department of Urology, National Institute of Kidney Diseases and Urology (NIKDU), Dhaka, Bangladesh from July 2017 to June 2019 over a period of 2 years. Sixty patients with BOO caused by benign prostatic hyperplasia scheduled for transurethral resection of prostate were included in this study. Patients were selected first by purposive sampling and were grouped into A and B with randomization. Group A patients underwent bipolar TURP while group B patients underwent sandwich method. Perioperative findings as well as IPSS Qmax and PVR after 3 months of operation were compared. Results: Operative time was significantly longer in TURP-TUVP group than in TURP group (P value 0.036).Post operative hospital stay was significantly longer in TURP group (P value <0.001). Catheterization time was significantly higher in TURP group (P value <0.001).Intra-operative irrigation was significantly higher in TURP-TUVP group (P value 0.001). Post operative irrigation time was significantly longer in TURP group (P value <0.001). Hemoglobin decrease was significantly higher in TURP group (P value <0.001). Similarly, sodium decrease was higher in TURP group than that of TURP-TUVP group but not statistically significant (P value 0.81).Clot retention was 2 (6.7%) in TURP group. Short-term follow up at 3 month showed no significant difference in IPSS in TURP and TURP-TUVP groups (P value 0.349), significantly higher Qmax in TURP-TUVP group (P value 0.022) and significantly higher PVR in TURP group (P value0.005) Conclusion:. TURP-TUVP procedure has higher operative time and intraoperative irrigation, but has significantly lower catheterization time, postoperative irrigation time, hemoglobin change and hospital stay. Bangladesh J. Urol. 2021; 24(2): 161-165